Host species shape the community structure of culturable endophytes in fruits of wild berry species (Vaccinium myrtillus L., Empetrum nigrum L. and Vaccinium vitis-idaea L.) - Nguyen, Minh-Phuong; Lehosmaa, Kaisa; Martz, Françoise; Koskimäki, Janne J; Pirttilä, Anna Maria; Häggman, Hely (FEMS microbiology ecology, 2021)
ABSTRACT Wild berries are interesting research subjects due to their rich sources of health-beneficial phenolic compounds. However, the internal microbial communities, endophytes, associated with the wild berry fruits are currently unknown. Endophytes are bacteria or fungi inhabiting inside plant tissues, and their functions vary depending on the host species and environmental parameters. The present study aimed to examine community composition of fungal and bacterial endophytes in fruits of three wild berry species (bilberry Vaccinium myrtillus L., lingonberry Vaccinium vitis-idaea L. and crowberry Empetrum nigrum L.) and the effects of host plant species and their growth sites on shaping the endophytic communities. We found that the endophytic community structures differed between the berry species, and fungi were predominant over bacteria in the total endophytic taxa. We identified previously unknown endophytic fungal taxa including Angustimassarina, Dothidea, Fellozyma, Pseudohyphozyma, Hannaella coprosmae and Oberwinklerozyma straminea. A role of soluble phenolic compounds, the intracellular components in wild berry fruits, in shaping the endophytic communities is proposed. Overall, our study demonstrates that each berry species harbors a unique endophytic community of microbes. Fruits of wild berry species bilberry, crowberry and lingonberry in Northern Europe harbor host-specific endophytic communities.